2007
DOI: 10.1007/s11294-006-9061-z
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of the Adoption and Extent of E-Commerce in Firms

Abstract: This work aims to explain firms’ decisions to adopt Internet-based e-commerce, and the extent to which the adopters subsequently implement e-commerce to commercialize their products and services. We examine various types of factors previously considered by the literature (competitive environment, organizational characteristics, strategic orientation, innovative capacity, managers’ characteristics, IT equipment possessed and the use made of it). The analytical model developed here on the basis of a sample of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 64 publications
1
15
2
3
Order By: Relevance
“…Likewise, when managers have a higher level of education, a firm will be more interested in implementing e-business (Rodríguez-Ardura, Meseguer-Artola & Vilaseca-Requena, 2007). Furthermore, given that the qualities of those in charge of the firm have a bearing on their management performance, it should be noted that those firms whose managers have a higher level of education are the ones that make greater use of e-business systems (Vilaseca., Torrent, Meseguer & Rodríguez, 2007).…”
Section: Human Capitalmentioning
confidence: 99%
“…Likewise, when managers have a higher level of education, a firm will be more interested in implementing e-business (Rodríguez-Ardura, Meseguer-Artola & Vilaseca-Requena, 2007). Furthermore, given that the qualities of those in charge of the firm have a bearing on their management performance, it should be noted that those firms whose managers have a higher level of education are the ones that make greater use of e-business systems (Vilaseca., Torrent, Meseguer & Rodríguez, 2007).…”
Section: Human Capitalmentioning
confidence: 99%
“…This is due, in most cases, to the fact that adoption occurs when the perception of the benefits of the innovation has been 3 The websites adoption in the Spanish agrifood firms Williams, 2006;Plana et al, 2006) but other works have not found that size plays a role in the ICT adoption (Hollenstein, 2004;Estapé-Dubreuil & TorreguitartMirada, 2014). The business sector has been included, considering that the particularities of each sector can influence in the decision making in a firm (Mcfarlane et al, 2003;Henderson et al, 2005;Baer & Brown, 2006;Mishra & Williams, 2006;Vilaseca et al, 2007a;Corrocher, 2011). Similarly, the firm's function in the supply chain can influence the adoption decision into one specific sector (Henderson et al, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The relationship between technology and ICT adoption is presented in the first a hypothesis of this research H1a : There is the significant relationship between technology factors and ICT adoption among Indonesian SMEs Organization is also associated with ICT. The literature reported that ICT adoption which may include employee, resources, strategic, and globalization 71,19,10,31 play a important role in the adoption of new technology 72,9,73 The study in SME's Vietnam, the determinant of e-commerce adoption is the employees' knowledge and the resources of enterprise. 19 Thefirm's strategy orientation can play an important role in the adoption of information technology.…”
Section: Ict Adoptionmentioning
confidence: 99%
“…19 Thefirm's strategy orientation can play an important role in the adoption of information technology. 74,73 The global reach of the internet makes morebeneficial, as a consequence firms with greaterglobalization are likely to use e-business. 31 The above discussion lead to the follwing hypothesis.…”
Section: Ict Adoptionmentioning
confidence: 99%